Exosome-Transported circRNA_0000253 Competitively Adsorbs MicroRNA-141-5p and Increases IDD - Jian Song; Zhen-Hao Chen; Chao-Jun Zheng; Ke-Han Song; Guang-Yu Xu; Shun Xu; Fei Zou; Xiao-Sheng Ma; Hong-Li Wang; Jian-Yuan Jiang (Elsevier, 2020)
The pathogenesis of intervertebral disc degeneration (IDD) is complex, and a better understanding of IDD pathogenesis may provide a better method for the treatment of IDD. Exosomes are 40-100 nm nanosized vesicles that are released from many cell types into the extracellular space. We speculated that exosome-transported circular RNAs (circRNAs) could regulate IDD. Exosomes from different degenerative grades were isolated and added to nucleus pulposus cells (NPCs), and indicators of proliferation and apoptosis were detected. Based on the previous circRNA microarray results, the top 10 circRNAs were selected. PCR was performed to determine the circRNA with the maximum upregulation. Competing endogenous RNA (ceRNA) analysis was carried out, and the sponged microRNA (miRNA) was identified. Further functional verification of the selected circRNA was carried out in vivo and in vitro. NPCs of different degenerative grades secreted exosomes, which could regulate IDD. circRNA_0000253 was selected as having the maximum upregulation in degenerative NPC exosomes. ceRNA analysis showed that circRNA_0000253 could adsorb miRNA-141-5p to downregulate SIRT1. circRNA_0000253 was confirmed to increase IDD by adsorbing miRNA-141-5p and downregulating SIRT1 in vivo and in vitro. Exosomal circRNA_0000253 owns the maximum upregulation in degenerative NPC exosomes and could promote IDD by adsorbing miRNA-141-5p and downregulating SIRT1.